Parvovirus B19 Infection due to over Immunosuppression in Kidney Transplant Recipients: Case Reports and Literature Review - Abdulrahman Altheaby; Malak Alotaibi; Nuha Alajlan; Ala Alshareef; Mohammed Alruwaymi; Ghaleb Aboalsamh; Mohammed F. Shaheen; Mohammed Alzunitan; Ziad Arabi (Case Reports in Transplantation)
Parvovirus B19 (PB19) is a single-stranded DNA virus that belongs to the Erythrovirus genus within the Parvoviridae family. Clinical presentations associated with PB19 infection vary greatly, depending on the infected individual’s age and hematologic and immunologic status. The limited data available regarding consensus on screening algorithms and indications in donors and recipients prior to kidney transplantation makes diagnosis and management challenging. We presented 3 cases of pure red cell aplasia due to parvovirus B19 after kidney transplant. These patients were diagnosed with severe normocytic, normochromic anemia (hemoglobin below 60 g/L) in the 1st 6 months posttransplant. A complete anemia work-up revealed low reticulocyte count and was otherwise inconclusive. All patients were diagnosed with pure red cell aplasia due to parvovirus B19. Two patients improved after receiving intravenous immunoglobulin 2 gm/kg given over 4 doses. Unfortunately, they relapse after few weeks and required additional doses of intravenous immunoglobulin in conjugation with reduction of their immunosuppressive medication. The third patient improved after holding mycophenolate mofetil (MMF) and did not require intravenous immunoglobulin. Whereas PB19 infection is typically self-limiting and associated with positive IgM serology in immunocompetent hosts, these cases highlight the importance of considering PB19 infection in the differential diagnosis of persistent anemia in immunocompromised patients and the challenges in confirming the diagnosis. Intravenous immunoglobulin (IVIG) can be an effective treatment in immunocompromised patients with primary or relapsed PB19 infection in conjunction with minimizing immunosuppressive medication. Further research and consideration are required to determine appropriate and targeted screening in donors and recipients in the peritransplantation period.